The effects of running shoe stack height on running style and stability during level running at different running speeds - Kettner, Cagla; Stetter, Bernd; Stein, Thorsten (Frontiers in Bioengineering and Biotechnology, 2025)
The footwear market contains a wide variety of running shoe solutions aiming at optimizing performance and minimizing injuries. Stack height is one of the most highly discussed design features of running shoes, but its effects are not yet well understood. This study investigated the effects of different shoes differing mainly in their stack heights (High: 50 mm, Medium: 35 mm and Low: 27 mm) on running style and stability during treadmill running at 10 and 15 km/h. A total of 17 healthy experienced runners participated. The kinematic data were recorded with a 3D motion capturing system. The running style was investigated with duty factor (DF) and leg length normalized to step frequency (SFnorm). Additionally, the ratio of landing to take-off duration, the lower body joint angle time series in the sagittal and frontal planes, the vertical center of mass oscillation (COMosc), and the stiffness parameters (kver and kleg) were compared for different conditions. The stability was analyzed using linear (i.e., discrete frontal ankle parameters) and nonlinear methods (i.e., Maximum Lyapunov Exponent for local dynamic stability of head, trunk, hip, and foot, and detrended fluctuation analysis of stride time). High resulted in longer ground contact relative to stride time (i.e., DF) compared to Low. The higher the stack height, the higher was the COMosc. Furthermore, High led to a longer foot eversion during stance compared to Medium. In addition, the local dynamic stability of the hip decreased with High in comparison with Low. The higher stack heights (≥35 mm) led to a lower SFnorm at 15 km/h but not at 10 km/h. The remaining shoe effects were independent of running speed. Findings showed that changes in stack height can affect running style. Furthermore, the highest stack height resulted in changes related with instabilities (i.e., longer foot eversion and lower hip dynamic stability) which may be a critical issue in terms of injuries and performance. However, this study did not include joint load analysis or running performance measures such as VO2. Future studies may benefit from combination of analysis approaches to better understand stack height effects on running injuries and performance.